The Influence of Brand Image, Product Quality and Lifestyle on Repurchase Intention Iphone Smartphones In The City Of Bandung - Erika Sofianti; Faizal Fardhani Sigarlaki (Community Engagement and Emergence Journal (CEEJ), 2025)
This study aims to examine the influence of brand image, product quality, and lifestyle on consumer decisions in repurchasing iPhone smartphones in the city of Bandung. The research method used is a quantitative approach with survey techniques through the distribution of online questionnaires using Google Form. Respondents were selected using the purposive sampling technique with the following criteria: at least 17 years old, have bought or used an iPhone, and reside in the city of Bandung. The number of respondents was 80 people. The results of the analysis show that partially, brand image, product quality, and lifestyle each have a positive and significant influence on repurchase intention. Simultaneously, these three variables have a significant effect. These findings show that positive brand perception, high product quality, and suitability with consumer lifestyles play an important role in driving iPhone product repurchase decisions among consumers in the city of Bandung.